Wind turbine and photovoltaic generating efficiency in Africa - Charles Fant (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
As the technology of climate-dependent energy sources is improving - both cheaper and more efficient - the energy sources are becoming more accessible for many of the nations in Africa. However, little is known about the underlying climate that would therefore be harvested by renewable technologies - namely, wind and solar - because these have not been well measured in this region in the past. Here, we present a study that uses publicly available data and methods to develop hourly onshore wind and solar photovoltaic (PV) electricity generation for the years 1979-2010. To do this, we use reanalysis climate data and well-trusted wind farm and solar PV simulation models as well as publicly available geospatial data. The primary purpose of this dataset is to be used in an energy-expansion-planning model of the African continent in a forthcoming study. We find that wind resources vary more over time and space than solar across Africa. Due mostly to these variations in wind resources, we find that the East African Power Pool shows the most potential for wind and solar and the Central African Power Pool shows the least potential. Using an aggregation of areas with the highest potential during the peak demand hours, we develop 'representative sites', one for each country. With these sites, we identify pairs of countries that have potential to participate in mutually beneficial power trade because these resources exhibit negative correlation in reference to each other. Most notably, we find that wind in Kenya and wind in Uganda, which are neighbouring countries, exhibit particularly beneficial characteristics in relation to each other.
Keywords: O13; O55; Q42; 330; renewable energy; energy planning; energy trade; Africa